Minimizing toxicity in early-stage testicular cancer treatment. Issue 2 (February 2012) - Singhera, Mausam; Lees, Kathryn; Huddart, Robert; Horwich, Alan
Testicular cancer is the paradigm of a curable malignancy, with 10-year survival rates exceeding 95%. Cisplatin-based regimes offer a survival gain of several decades of life; however, measures of outcomes in testicular cancer are evolving. Survivorship issues are becoming increasingly important in this young adult population. Long-term risks of second malignancy and cardiovascular disease secondary to chemotherapy and radiotherapy have been extensively documented, leading to an increased uptake of surveillance. However, the optimal surveillance schedule is not universally agreed upon. Research into modalities to detect relapse and frequency is ongoing. Reducing the treatment burden with fewer cycles of chemotherapy (one cycle of bleomycin, cisplatin and etoposide instead of two for stage I high-risk nonseminomatous tumors) or less toxic alternatives (carboplatin instead of radiotherapy for stage I seminomas) is currently being explored. This article details the toxicities associated with the diagnosis and treatments of early-stage testicular cancer and current strategies used to minimize toxicity while retaining the excellent cure rates.